Public Sector Reforms and Human Resources for Health in Thailand : An Exploration of Impacts, Issues and Options for Moving Forward - World Bank (World Bank, 2012)
This report responds to a Ministry of Public Health (MOPH) request to the World Bank to conduct exploratory work to examine the impacts of public sector reforms on human resources for health (HRH), with the aim of identifying areas where further analytical work may be useful. A World Bank team interviewed a range of stakeholders: senior officials of MOPH, the Office of the Civil Service Commission (OCSC), the Office of the Public Sector Development Commission (OPDC), and the Nursing Council; directors and managers of district, provincial, and regional hospitals and one health center; health care workers; nursing instructors and students; as well as expert observers and academicians. Interviews were conducted in Bangkok and three provinces (Mae Hong Son, Khon Kaen, and Songkhla) in February-March 2010, with participation of researchers from MOPH's Health Intervention and Technology Assessment Program (HITAP). The information in this report is based on interviews, and a review of key pieces of legislation and available English-language literature and some Thai-language literature. We were not able in this brief initial foray to conduct a comprehensive in-depth review of regulations nor of all related Thai-language research that has been conducted by a variety of entities. With this in mind, we ask for readers? forbearance and welcome comments. This report consists of a concise main text that presents key issues and stakeholder perspectives, and suggests further analytical work for consideration. A series of annexes provide background about the fundamental structure and features of health sector employment, sample earnings data, and short profiles of individual health workers interviewed by the team. Readers who are not familiar with the main features of Thailand's HRH may wish to review the annexes prior to reading the main text.